2021
DOI: 10.1002/elps.202000263
|View full text |Cite
|
Sign up to set email alerts
|

3‐(4‐Carboxybenzoyl)quinoline‐2‐carboxaldehyde labeling for direct analysis of amino acids in plasma is not suitable for simultaneous quantification of tryptophan, tyrosine, valine, and isoleucine by CE/fluorescence

Abstract: Capillary electrophoresis coupled to LED-induced fluorescence detection is a robust and sensitive technique used for amino acids (AA) analysis in biological media, after labeling with 3-(4-carboxybenzoyl)quinoline-2-carboxaldehyde (CBQCA). We wanted to quantitate in plasma tryptophan (Trp), tyrosine (Tyr), valine (Val), and isoleucine (Ile). Among the different labeled AA-CBQCA, Trp has the lowest fluorescence yield, which makes its detection and quantification very difficult in biological samples such as plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The majority of AAs do not produce signals in UV/VIS photometric or fluorescence detection and therefore it is very favorable to employ universal capacitively coupled contactless C 4 D. The application of CE with C 4 D for analysis of AAs in biological fluids did not require derivatization of the analyte [34, 109,110]. Many research articles investigating the applications of CE with C 4 D for determination of AAs in various biological fluids reported in scientific literature [89,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. Summaries of these applications are shown in Table 3.…”
Section: Amino Acids (Aas)mentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of AAs do not produce signals in UV/VIS photometric or fluorescence detection and therefore it is very favorable to employ universal capacitively coupled contactless C 4 D. The application of CE with C 4 D for analysis of AAs in biological fluids did not require derivatization of the analyte [34, 109,110]. Many research articles investigating the applications of CE with C 4 D for determination of AAs in various biological fluids reported in scientific literature [89,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. Summaries of these applications are shown in Table 3.…”
Section: Amino Acids (Aas)mentioning
confidence: 99%
“…The baseline of HAc is found to be stable; therefore, HAc BGEs have been applied in many applications for the separation of AAs as well as biogenic amines [111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. The use of HAc with hydroxypropyl-βcyclodextrin and tween at pH 2.6 and with dextran for the analysis of carnitine and acylcarnitine [119] and heparin [122]. The details on analyses of these compounds with CE-C 4 D can be found in Table 3.…”
Section: Amino Acids (Aas)mentioning
confidence: 99%
See 2 more Smart Citations
“…With the continuous development of pretreatment techniques, CE combined with different detection methods has been widely used in various fields. The researchers investigate the implementations and advancements of CE in recent three years and found that CE was mainly coupled with UV detection [15], fluorescence detection [16], MS [17][18][19], and electrochemical detection [20] including conductivity detection (CD) [21,22] and amperometric detection (AD) [23] for the analysis of some substances in different fields. These fields mainly consist of environmental analysis [24], pharmaceutical analysis [25][26][27], clinical analysis [28,29], and food analysis [30,31].…”
Section: Introductionmentioning
confidence: 99%